Marco Valerio Marcial, Antología de epigramas, traducción y nota preliminar Pedro Conde Parrado, Gijón, Ediciones Trea, 2014, 134 pp. ISBN 978-84-9704-813-2 (Minerva, 2019)
Review: Marco Valerio Marcial, Antología de epigramas, traducción y nota preliminar Pedro Conde Parrado, Gijón, Ediciones Trea, 2014, 134 pp. ISBN 978-84-9704-813-2